"The Effects of Urbanization on Local Biodiversity and Ecosystem Services" - Rifat Khursheed (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
Urbanization is a dominant force shaping ecological dynamics worldwide. As urban areas expand to accommodate growing populations and economic activities, natural landscapes are transformed, often at the cost of local biodiversity and the ecosystem services they support. This paper explores the multifaceted impacts of urbanization on biodiversity, focusing on habitat loss, fragmentation, pollution, and species displacement. It also evaluates the degradation of ecosystem services such as pollination, air and water purification, climate regulation, and cultural benefits. The study highlights case examples, proposes mitigation strategies including green urban planning and ecological restoration, and stresses the importance of balancing development with conservation for sustainable urban growth.